2016
DOI: 10.1007/s10450-016-9761-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of sorption processes of strontium on the synthetic hydroxyapatite

Abstract: Adsorption of 90 Sr on hydroxyapatite is important in many fields of life. The aim of the paper was to discuss the changes in the double electrical layer at the hydroxyapatite/electrolyte solution interface during Sr ions adsorption and to establish the relations between time and adsorption on this material. Hydroxyapatite was prepared by the wet method, characterized by the X-ray diffraction and accelerated surface area and porosimetry methods. Studies of adsorption were carried out using 90 Sr isotopes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
1
28
0
8
Order By: Relevance
“…10. The effect of adsorption on the specific surface area and porosity was different from that observed for the of hydroxyaptite sample with the adsorbed Sr 2+ ions (Janusz and Skwarek 2016). This difference may result from the of size of adsorbed ions because Sr 2+ adsorption leads to a significant decrease in the crystal size and changes in aggregation of hydroxyapatite particles.…”
Section: Pxrd Study Of the Ba 2+ Ion Adsorption Of Ion On Hydroxyapatitementioning
confidence: 60%
See 1 more Smart Citation
“…10. The effect of adsorption on the specific surface area and porosity was different from that observed for the of hydroxyaptite sample with the adsorbed Sr 2+ ions (Janusz and Skwarek 2016). This difference may result from the of size of adsorbed ions because Sr 2+ adsorption leads to a significant decrease in the crystal size and changes in aggregation of hydroxyapatite particles.…”
Section: Pxrd Study Of the Ba 2+ Ion Adsorption Of Ion On Hydroxyapatitementioning
confidence: 60%
“…This course of adsorption and the time of achieving equilibrium differ from that of the other divalent ions e.g. Sr 2+ , Cd 2+ , Co 2+ where their adsorption on hydroxyapatite proceeds via two steps; the first one fast and the second slow (Janusz and Skwarek 2016;Skwarek and Janusz 2016;Smiciklas et al 2006). Different adsorption kinetics of Ba 2+ ions may be due to the ionic radius of Ba 2+ ions that fall outside the limit of cation radius which results the exchange in the crystal structure will not deform it significantly (Reichert and Binner 1996).…”
Section: Kinetics Of Barium Ions Adsorption At the Hydroxyapatite/elementioning
confidence: 92%
“…Nano-hydroxyapatite [Ca 10 (OH) 2 •(PO 4 ) 6 ] plays a significant role in both isolation of dissolved metals and their transformation in soil into less soluble phases. The literature presents the papers on strong affinity of hydroxyapatite for strontium and other metals (Janusz and Skwarek 2016;Skwarek and Janusz 2016;Skwarek 2015). Hydroxyapatite is an ideal material for long-term binding of contaminates due to its high sorption capacity for the actinide series and heavy metals, poor solubility in water, high stability under reducing and oxidizing conditions, accessibility, and low preparation cost.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Hap, owing to its crystal structure and chemical composition, can adsorb metal ions by several mechanisms, including ion exchange, surface complexation, diffusion through the solid material, and dissolution-precipitation [66]. This allows for the purification of aqueous solutions of many metals, for example Cu(II) [67], Pb(II) [68], Sr(II) [69], as well as Cr(III) [70] and Al(III) [66]. The ability of Al 2 O 3 coatings for removing Al ions from immersion solution may result from its amorphous structure and possible non-stoichiometric chemical composition.…”
Section: Barrier Propertiesmentioning
confidence: 99%